WHIP, BABIP, and FIP: the role of radio broadcasters in the diffusion of advanced statistics in Major League Baseball broadcasts - Nehm, Eric (Kansas State University, 2015)
The purpose of this study was to take a closer look at the use of advanced statistics in Major League Baseball (MLB) radio broadcasts and the possible effects usage could have on the roles of MLB broadcasters. This study used a theoretical framework supported by role theory and diffusion of innovations theory. The study employed in-depth interviews of eight MLB radio broadcasters to get a better understanding of the broadcasters’ thoughts on the value of advanced statistics, how using advanced statistics could affect their role as a broadcaster, the factors that influence the potential inclusion of advanced statistics in their broadcasts, and ultimately, whether broadcasters perceived advanced statistics as a trend or a fad. The interviews revealed a number of things about the baseball broadcasting industry with disagreements appearing in regards to techniques in using advanced statistics in broadcasts and the value of advanced statistics to listeners. Despite the disagreements, the most important finding was the unanimous belief that advanced statistics are not a fad, but rather something that will remain a part of baseball broadcasts going forward.
Keywords: sports broadcasting; broadcasting; broadcasting roles; advanced statistics; sabermetrics; sports broadcast content; Mass Communications (0708)